2020
DOI: 10.1021/acs.analchem.9b05841
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall Au(0) Inserted Hollow PCN-222 MOF for The High-Sensitive Detection of Estradiol

Abstract: Here, the effect of morphology on the electrocatalytic activity of metal–organic framework (MOF) was investigated. Post synthetic gold (Au) insertion was done into hollow PCN-222 (HPCN-222) and solid PCN-222 (SPCN-222) frameworks by a simple hydrothermal method. The crystalline nature, chemical composition, and morphologies of the synthesized MOFs were characterized by PXRD, XPS, and TEM. Electrochemical characterizations were done by cyclic voltammetry and electrochemical impedance spectroscopy. The excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 46 publications
(70 reference statements)
4
47
0
2
Order By: Relevance
“…Besides, electrochemical activity and charge transferability of hollow MOFs could be also utilized to construct electrochemical sensing platforms for detection of medical molecules like antimicrobial agent nitrofurazone (NFZ), whose excessive utilization and deficient management would lead to severe consequences on ecosystems and human health [97, 98] . Liu et al.…”
Section: Applicationsmentioning
confidence: 99%
“…Besides, electrochemical activity and charge transferability of hollow MOFs could be also utilized to construct electrochemical sensing platforms for detection of medical molecules like antimicrobial agent nitrofurazone (NFZ), whose excessive utilization and deficient management would lead to severe consequences on ecosystems and human health [97, 98] . Liu et al.…”
Section: Applicationsmentioning
confidence: 99%
“…Besides,e lectrochemical activity and charge transferability of hollow MOFs could be also utilized to construct electrochemical sensing platforms for detection of medical molecules like antimicrobial agent nitrofurazone (NFZ), whose excessive utilization and deficient management would lead to severe consequences on ecosystems and human health. [97,98] Liu et al thus prepared hollow MIL-101 (Cr) by etching method as an electrochemical sensor for detection of NFZ, which could be electrochemically oxidized by the hollow MOF. [97] Hollow MIL-101 (Cr) displayed much higher sensitivity in the range of in the range of 0.030-55 mM with alimit of detection (LOD) of 10 nM than solid MIL-101 (Cr) (Figure 17 e).…”
Section: Sensing Applicationsmentioning
confidence: 99%
“…Theh ierarchically porous structure of hollow MIL-101(Cr) with large inside cavity benefitted the accumulation of NFZ and the inner layer surface provided more catalytically active sites.T hus,h ollow MIL-Cr (101) demonstrated high efficiencyf or electro-sensitive oxidation of NFZ with wide linear relation range.Likewise,W ang et al developed ahollow PCN-222 MOF with Au cluster insertion as an electrochemical sensor and found that it presented high electro-oxidation activity for estradiol, which was af emale sex hormone that would lead to implications in breast tumors and other endocrinal disorders. [98] Similarly,t he hollow structure and well-defined functionalities of hollow PCN-222 composite also provided abundant adsorbing sites for analyte and enhanced interfacial charge transfer. Thus,t he oxidizing current could reach high enough for detection of small amount of estradiol with high sensitivity (wide linear range 0.01 nM-210 mMand trace level LOD of 0.5 nM) than solid MOF (Figure 17 f).…”
Section: Sensing Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, nanomaterials have attracted worldwide attention and have been widely used to modify electrochemical sensing electrodes. As one of the most popular materials at present, the conductive nano-Metal Organic Framework (MOFs) (Campbell and Dincȃ, 2017;Biswas et al, 2020;Ko et al, 2020;Suwannakot et al, 2020) have many advantages, such as simple synthesis process, environmental friendliness, adjustable structure and so on, especially its excellent conductivity, which has attracted extensive attention (Ko et al, 2017;Fang et al, 2018;Xie et al, 2020). Metal-catecholates (M-CATs) are a kind of conductive MOF composed of HHTP ligands and central metal ions (Miner et al, 2018;Zhang et al, 2018Zhang et al, , 2019Guo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%